(untitled) (REGE Revista de Gestão, 2020)
Purpose – In 2008, a phenomenon emerged in online retail that attracted the attention of many people, creating a new virtual model of commerce. This phenomenon was called online group buying and arrived in Brazil in 2010. The purpose of this study was to identify the factors that affect satisfaction and loyalty to group buying sites. Design/methodology/approach – Through structural equation modeling, the relationships between the attractiveness of discount rates, service quality, popularity, online brand image, antecedent word of mouth (WOM), creativity and trust in relation to consumer general satisfaction, declared loyalty, repurchase intention and positive WOM were observed. A total of 727 valid questionnaires were collected from online group buyers to test the 11 hypotheses proposed in this study. Findings – The main contribution of this study was that it identified the strong influence of service quality, popularity and online brand image on consumer general satisfaction, and the influence of service quality, trust and general satisfaction on repurchase intention. It also identified the influence of trust, creativity and general satisfaction on declared loyalty, and finally, the influence of trust and general satisfaction on positive WOM. Research limitations/implications – Because of the extensive and robust model, other statistical interactions among the constructs were gauged. It is possible that new structures and paths for alternative models can be proposed in the future with the inclusion of new relationships not analyzed in the present study. Furthermore, future studies should consider testing the generated model in other countries, as the particular features of collective purchasing in Brazil should be taken into account. Practical implications – In addition to being concerned with the attractiveness of discounts, marketing managers of group buying sites should concentrate their efforts on strengthening perceived quality, image, trust and the creativity of the site to ensure customer loyalty. Social implications – The online group buying business model that was established in Brazil differs significantly from the American and European models. As many online group buying studies have been conducted in these markets, Brazilian consumers will enjoy substantial gains in the quality of the service provided by collective purchasing sites through the development of actions that focus on improving the factors that affect these consumers. Originality/value – The originality of this study lies in the development of a single model that tests a set of factors gauged separately in other studies related to online purchase behavior in a broader perspective.